The Recurrent Quest: Demeter and Persephone in Modern Ireland - Bennett, Karen (2003)
This article examines the myth of Demeter and Persephone in two poems from modern Ireland, Eavan Boland's 'The Pomegranate' and Ciaran Carson's 'Ascalaphus'.